The meaning of work: an analysis in the light of The Generations X and Y - Teixeira, Ana Paula Pydd (2014)
The sense of work is a fundamental issue when we take into consideration that the very labor organization changes constantly, bringing out concerns to the individuals. This article analyzed the meaning of work for the generations X and y. A survey research was conducted with two groups, one belonging to the generation X and another to the generation Y. Characteristics attributed to the generation Y appeared with greater significance among the respondents of the generation X and the similarity of the averages of some answers indicates that the generations share many values, which commonly is not stated.